Characterization of organic nitrate constituents of secondary organic aerosol (SOA) from nitrate-radical-initiated oxidation of limonene using high-resolution chemical - Iodide-HR-ToF-CIMS Data from NO3-initiated Oxidation of Limonene - Hallquist, Mattias (University2, 2018)
The gas-phase nitrate radical (NO3*) initiated oxidation of limonene can produce organic nitrate species with varying physical properties. Low-volatility products can contribute to secondary organic aerosol (SOA) formation and organic nitrates may serve as a NOx reservoir, which could be especially important in regions with high biogenic emissions. This work presents the measurement results from flow reactor studies on the reaction of NO3 with limonene using a High-Resolution Time-of-Flight Chemical Ionization Mass Spectrometer (HR-ToF-CIMS) combined with a Filter Inlet for Gases and AEROsols (FIGAERO). Major condensed-phase species were compared to those in the Master Chemical Mechanism (MCM) limonene mechanism, and many non-listed species were identified. The volatility properties of the most prevalent organic nitrates in the produced SOA were determined. Analysis of multiple experiments resulted in the identification of several dominant species (including C10H15NO6, C10H17NO6, C8H11NO6, C10H17NO7, and C9H13NO7 ) that occurred in the SOA under all conditions considered. Additionally, the formation of dimers was consistently observed and these species resided almost completely in the particle phase. The identities of these species are discussed, and formation mechanisms are proposed. Cluster analysis of the desorption temperatures corresponding to the analyzed particle phase species yielded at least five distinct groupings based on a combination of molecular weight and desorption profile. Overall, the results indicate that the oxidation of limonene by NO3 produces a complex mixture of highly oxygenated monomer and dimer products that contribute to SOA formation.

Purpose:

To explore the chemical composition of low-volatility gas and aerosol-phase species, formed from mixtures of N2O5 and limonene, as measured by a High Resolution Time-of-Flight Chemical Ionization Mass spectrometer (HR-ToF-CIMS) coupled to a Filter Inlet for Gases and AEROsols (FIGAERO) inlet.

The objectives of this work were three-fold namely, to: (i) determine the molecular formula of major nitrate species, produced from the reaction of limonene with NO3, that could contribute significantly to SOA formation and growth, (ii) compare the distribution of measured products to that of the expected products (formed via the Master Chemical Mechanism (MCM)) to identify any discrepancies in the mechanistic understanding of nitrate formation from limonene, and (iii) categorize, via cluster analysis, the thermodynamic desorption data measured for selected condensed-phase species.

The gas-phase nitrate radical (NO3*) initiated oxidation of limonene can produce organic nitrate species with varying physical properties. Low-volatility products can contribute to secondary organic aerosol (SOA) formation and organic nitrates may serve as a NOx reservoir, which could be especially important in regions with high biogenic emissions. This work presents the measurement results from flow reactor studies on the reaction of NO3 with limonene using a High-Resolution Time-of-Flight Chemical Ionization Mass Spectrometer (HR-ToF-CIMS) combined with a Filter Inlet for Gases and AEROsols (FIGAERO). Major condensed-phase species were compared to those in the Master Chemical Mechanism (MCM) limonene mechanism, and many non-listed species were identified. The volatility properties of the most prevalent organic nitrates in the produced SOA were determined. Analysis of multiple experiments resulted in the identification of several dominant species (including C10H15NO6, C10H17NO6, C8H11NO6, C10H17NO7, and C9H13NO7 ) that occurred in the SOA under all conditions considered. Additionally, the formation of dimers was consistently observed and these species resided almost completely in the particle phase. The identities of these species are discussed, and formation mechanisms are proposed. Cluster analysis of the desorption temperatures corresponding to the analyzed particle phase species yielded at least five distinct groupings based on a combination of molecular weight and desorption profile. Overall, the results indicate that the oxidation of limonene by NO3 produces a complex mixture of highly oxygenated monomer and dimer products that contribute to SOA formation.

Syfte:

To explore the chemical composition of low-volatility gas and aerosol-phase species, formed from mixtures of N2O5 and limonene, as measured by a High Resolution Time-of-Flight Chemical Ionization Mass spectrometer (HR-ToF-CIMS) coupled to a Filter Inlet for Gases and AEROsols (FIGAERO) inlet.
Characterization of organic nitrate constituents of secondary organic aerosol (SOA) from nitrate-radical-initiated oxidation of limonene using high-resolution chemical - Iodide-HR-ToF-CIMS Data from NO3-initiated Oxidation of Limonene
Keywords: Nitrates; Nitrater; Mass Spectrometry; Masspektrometri; AEROSOLS; NITRATE PARTICLES; ORGANIC PARTICLES; OXIDATION/REDUCTION; SCIENCE AND TECHNOLOGY; VETENSKAP OCH TEKNOLOGI; Natural Sciences; Naturvetenskap; Chemical Sciences; Kemi